BIOSTRATIGRAFIA A NANNOFOSSILI CALCAREI CALPIONELLIDI E FORAMINIFERI PLANCTONICI DELLA MAIOLICA (TITONIANO SUPERIORE—APTIANO) NELLE PREALPI BRESCIANE (ITALIA SETTENTRIONALE) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
A detailed lithostratigraphic and micropaleontological study was undertaken on the Maiolica formation outcropping in the NW of Brescia. The Maiolica mainly consists of whitish to pale brown grey pelagic limestones with shaly interbeds in its upper portion; chert nodules and lenses occur within the limy beds whereas chert layers are interbedded, the color of which varies from pinkish to grey to black. Frequent bluish layers consisting of radiolarian silt occur in the upper portion of the Maiolica.
Keywords: Biostratigraphy; Calcareous nannofossils; Calpionellids; Planktonic foraminifers; Upper Jurassic; Lower Cretaceous; Lombardian Prealps.